The Effect of Physical Experience and Integrated Information on Customer Purchase Behavior in Online-to-Offline Commerce - Christine, christine; Jimmy, So Yohanes; Utomo, Prio (Bina Nusantara University, 2025)
Online-to-Offline (O2O) is a business model increasingly being developed and widely implemented by companies in Indonesia. Therefore, the research examines the factors influencing purchasing behavior in Indonesian O2O commerce through economic theories, namely Perceived Risk and Perceived Benefit. The research procedures were carried out using a quantitative approach, and the data obtained were analyzed with Partial Least Square Structural Equation Modeling. The sample data was selected using a purposive sampling method and collected through an online survey instrument from 248 millennial customers who had made O2O purchases. The results show that all exogenous variables had significant effects, except for Physical Experience, which did not significantly affect Perceived Risk. Meanwhile, Integration Online-to-Offline Information (IOOI) had the most significant impact on enhancing customer purchase intention. The results also showed that Perceived Benefits had a significant impact on customer purchase intention. This research offers a novel perspective by exploring how integrated customer behavior across digital and physical channels influenced purchasing decisions within the Indonesian context, where existing literature was limited. The results provide valuable insights for companies in formulating strategies to deliver effective physical experiences and IOOI. Companies should ensure that the information available across online and offline channels is complementary and consistent to maximize customer purchase intention.